Overview of Islamic Finance in Uzbekistan: Challenges, and Prospects (European Journal of Economics, Finance and Business Development, 2023)
This research paper aims to explore the development process of Islamic finance in Uzbekistan, focusing on the opportunities, challenges, and prospects associated with its growth. Islamic finance is gaining momentum worldwide, offering an alternative financial system that adheres to Islamic principles. Uzbekistan, as a predominantly Muslim country with a growing economy, has recognized the potential of Islamic finance in promoting financial inclusion, economic stability, and sustainable development. This paper provides an overview of the current state of Islamic finance in Uzbekistan, analyzes the opportunities it presents, identifies the challenges hindering its progress, and outlines the prospects for its future development. The research is based on a comprehensive review of existing literature, policy documents, and interviews with relevant stakeholders.